2017
DOI: 10.22324/ijhrdppr.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Learning-Oriented Leadership: Managers as Facilitators of Human Resource Development in Daily Work

Abstract: The aim of this article is to provide theoretical and empirical insights concerning the role of managers in facilitating their employees' learning and development at work. The empirical basis of the article is two case studies of industrial companies in which managers were interviewed and observed. The results indicate that managers use combinations of different activities (planned, partially planned and spontaneous) and roles (the supporter, the educator and the confronter) to facilitate learning in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 39 publications
(91 reference statements)
0
31
0
Order By: Relevance
“…However, even some 'ineffective behaviours' (e.g. being authoritarian) may well trigger employee learning in some situations (Wallo 2017). For example, managers might use threats of punishment to influence poor performers to acquire the skills and knowledge necessary to improve their work performance.…”
Section: Facilitation Of Informal Workplace Learningmentioning
confidence: 99%
“…However, even some 'ineffective behaviours' (e.g. being authoritarian) may well trigger employee learning in some situations (Wallo 2017). For example, managers might use threats of punishment to influence poor performers to acquire the skills and knowledge necessary to improve their work performance.…”
Section: Facilitation Of Informal Workplace Learningmentioning
confidence: 99%
“…Another prominent topic in the articles concerned different approaches to assessing employees’ current competencies in relation to competence frameworks—both organization-specific and profession-specific frameworks. These studies also largely relied on quantitative assessment approaches (e.g., Bing-Jonsson et al, 2016; Takase et al, 2015); however, other studies focused on qualitative assessment methods, such as performance reviews and salary discussions (Bednall et al, 2014; Wallo, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, performance appraisal interviews are seldom examined from a quality standpoint. For example, Wallo (2017) found that much of the time during interviews is often focused on social talk rather than on discussions relating to whether employees are applying trained capabilities in their jobs, the nature of employees' learning needs and opportunities for competence development. This lack of attention to quality of implementation is illustrated by the case study participants' comments.…”
Section: Table 2 (Continued)mentioning
confidence: 99%
“…Based on studies of FLMs in manufacturing companies, Wallo (2008;2017) and Wallo, Ellström and Kock (2013) distinguished between performance-oriented and developmentoriented leadership. The former type focused mainly on improving employees' performance through adaptive learning and building on their current knowledge; this was the predominating orientation in both studies.…”
Section: Related Researchmentioning
confidence: 99%
“…A common theme of these two strands of research is the potentially important role of FLMs in facilitating employee learning and development and an envisioned shift away from their role as subject-matter experts and controllers towards a more educative and supportive role (Ellinger, Watkins and Barnas, 1999;Hamlin, Ellinger and Beattie, 2006). Studies have described this allegedly new management role in terms of coaching (Hamlin et al, 2006), knowledge leadership (Viitala, 2004), or learning-oriented leadership (Döös, Johansson and Wilhelmson, 2015;Wallo, 2008;2017). This latter term will be used in this article.…”
Section: Introductionmentioning
confidence: 99%